Lullaby: A Prelude to Initial Learning - Vaidya, Dharmanshu (THE PRIMARY TEACHER, 2019)
The tradition of lullaby is found in almost all cultures. Everyday interaction with different sounds and the features of the singer generates a psychic comfort for the young child. The amount of time spent with the child proportionately increases familiarity. In other words, lullaby can situate a scope for affiliation outside biological mandate. Lullabies can prove to be a rich resource for enhancing multi-cultural breadth in an early childhood programme. This is all the more relevant in cases of transitional distress experienced by some young children, or to provide support to children from various linguistic backgrounds, or to make children welcome to schooling.